2020
DOI: 10.1007/978-3-030-54595-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Farm Area Segmentation in Satellite Images Using DeepLabv3+ Neural Networks

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, there are a variety of semantic segmentation models such as U-Net, FCN, SegNet, PSPNet, and DeepLab series, etc. Among the various semantic segmentation models, DeepLabV3+ had been extensively used in many studies [18][19][20] and can obtain more accurate contours. Therefore, DeepLabV3+ was chosen as the model for the recognition of grapes.…”
Section: Motivationmentioning
confidence: 99%
“…However, there are a variety of semantic segmentation models such as U-Net, FCN, SegNet, PSPNet, and DeepLab series, etc. Among the various semantic segmentation models, DeepLabV3+ had been extensively used in many studies [18][19][20] and can obtain more accurate contours. Therefore, DeepLabV3+ was chosen as the model for the recognition of grapes.…”
Section: Motivationmentioning
confidence: 99%
“…Another criterion that is used for the proposed semisupervised frame work is the dissimilarity of the segmented area to the labelled patches. This shown in (2), where is the total number of clusters and is the total number of segments clustered into cluster and is the 13 length feature vectors of the segment of cluster and is the feature vector of cluster .…”
Section: F Evaluation Of Segmentationmentioning
confidence: 99%
“…It finds application in many domains. Examples are urban data analysis and planning [1], digital agriculture [2,3], environmental studies and hazards analysis [4] and traffic and navigation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep convolutional neural network algorithms learn different image features by building a hierarchy of data representation, which make this type of algorithm very efficient in processing complex real-world images such as remote sensing images. Thus, deep convolutional neural networks have been applied to several tasks in extracting information from satellite and aerial images such as road extraction [8,9], farm segmentation [10], building footprint segmentation [11][12][13][14] and building damage assessment [15,16]. These existing research studies have shown that the end-to-end learning approach based on deep learning algorithms significantly improved the accuracy of automatic building footprint extraction in comparison to more traditional methods that are based on the features engineering approach.…”
Section: Introductionmentioning
confidence: 99%